The in-service teachers’ reflection on the implementation of problem-based learning in the teacher professional education program at Universitas Pancasakti Tegal - Sumartono , Sumartono; Fitriati , Sri Wuli; Wahyuni , Sri; Sakhiyya, Zulfa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study explores the reflections of in-service teachers on the implementation of Problem-Based Learning (PBL) in the Teacher Professional Education Program (TPEP). With the increasing demand for 21st-century teaching skills, PBL has emerged as an effective instructional method to foster critical thinking, problem-solving, and student engagement. Using a qualitative approach, this research collected data from three in-service teachers through semi-structured interviews, classroom observations, and reflective journals. The findings highlight the benefits of PBL, including enhanced student motivation, collaboration, and a deeper understanding of learning materials. However, challenges such as time constraints, technical difficulties, and student adaptation to PBL were also identified. Teachers implemented solutions such as structured time management, technology integration, and active monitoring of student participation. Follow-up plans emphasize continuous reflection, evaluation, and adaptation to optimize the effectiveness of PBL in the classroom. The study underscores the importance of professional development in equipping teachers with the necessary skills to implement innovative teaching approaches. By addressing the challenges of PBL through strategic planning and ongoing support, teachers can enhance student learning outcomes and improve the overall teaching process.